The Effects of Abutment Finish Lines on the Penetration Characteristics of Elastomers into the Simulated Gingival Sulcus - Jaroenpiboon, Atiwat; Apinsathanon, Pongsakorn; Na Nan, Pheeradej; Aimjirakul, Napapa (European Journal of Dentistry, 2023)
Objective The aim of this study was to determine the effect of finish lines on the penetration ability of polyether and polyvinyl siloxane impression material into the simulated gingival sulcus.Materials and Methods Three types of finish line (chamfer, deep chamfer, and radial shoulder) were impressed with two types of elastomeric impression material (polyether and polyvinyl siloxane) using a two-step impression technique. Ten samples of each finish line were prepared and then separated into two groups of impression material: polyether and polyvinyl siloxane. The model of the simulated gingival sulcus had a width of 0.1 mm and a depth of 3.5 mm with a subgingival finish line of 0.5 mm. The effect of the finish lines on the penetration ability of these impression materials was analyzed using a two-way analysis of variance (ANOVA) and Tukey's multiple comparison tests at a statistically significant level of 0.05.Results A two-way ANOVA revealed a significant difference among finish lines, impression materials, and their interaction. The deep chamfer and radial shoulder finish lines displayed significantly higher penetration ability than the chamfer finish line. Moreover, polyether revealed significantly higher penetration ability than polyvinyl siloxane.Conclusion The finish lines affected the penetration ability of the impression materials. Therefore, the simulated gingival sulcus model demonstrates that it is an effective way of examining impression materials' penetration abilities.
Keywords: dental; abutment; finish line; impression materials; penetration ability